Comparison of Gastrocnemius Muscle Strength between Basketballs and Non-basketball Player - Titing Nurhayati; Sharmili Mohanan; Marietta Shanti Prananta (Althea Medical Journal, 2019)
Background: Basketball is one of the best aerobic-predominant exercises and the most important muscle used in this sport is the gastrocnemius muscle. This muscle plantar flexes the ankle when the knee is extended to maintain the balance and to stabilize the body during vigorous movements. Furthermore, the gluteus, quadriceps, hamstrings, and calves may get activated when running up and down the court and jump in the air when doing basketball training. This study was conducted to compare the gastrocnemius muscle strength in basketball and non-basketball players.Methods: This analytical study was to measure the gastrocnemius muscle strength in basketball (n=16) and non-basketball (n=16) players, using hand-held dynamometer (HHD). Gender, weight, height, Body Mass Index (BMI) and maximal gastrocnemius muscle strength were recorded and compared between groups. The study was conducted from August to October 2013 in the Faculty of Medicine, Universitas Padjadjaran.Results: The maximal gastrocnemius muscle strength showed no significant differences both in basketball and non-basketball players for females and males with p-value 0.092 and 0.711, respectively.Conclusions: There is no significant difference in gastrocnemius muscle strength between basketball and non-basketball players in males as well as in females. Presumably, there are other muscles that take parts to develop leg power by doing the right weight-training exercises.